Analysis of genetic diversity in Colombian buffalo herds (2010)
ABSTRACT: Estimates of genetic diversity provide useful information on the genetic structure of animal populations, useful for the design of improvement strategies to impact traits of economic interest. They can also be used for implementing conservation and restoration policies regarding the sustainable use of genetic resources. The aim of this study was to characterize the genetic structure of buffalo population (Bubalus bubalis) in the most representative Colombian provinces by using 10 microsatellite markers. A total of 588 individuals were sampled from 12 buffalo herds. The MGTG7 and ETH225 microsatellites were monomorphic. Eighty seven alleles were observed for all the loci. The average number of alleles was 10.9 ± 3.6 and the effective average number of alleles was 3.9 ± 1.4. The PIC values ranged between 0.5 and 0.8, and the probability of exclusion over all loci was over 99.99%. The highest value for the Ho population was 0.68, and the lowest was 0.60. The GST value for the total loci was 0.062, indicating a very low level of genetic structure among subpopulations. Values for genetic distance between populations and racial groups were very low, suggesting there is still a genetic mix within buffalo herds in the analyzed population.